PENGARUH STRATEGI PEMASARAN MELALUI TIKTOK TERHADAP MINAT BELI KONSUMEN: STUDI LITERATUR - Annisa, Febri; Mochammad Reza Fadli; Novia Suherman; Ida Farida Adi Prawira (Universitas Haji Sumatera Utara, 2024)
TikTok, with over 1 billion global active users, has become the platform of choice for business marketing, especially in Indonesia with 22.2 million active users. Businesses use TikTok to create engaging content, collaborate with influencers, and run paid advertisements. These marketing strategies aim to enhance brand awareness and foster interactions with consumers. Several studies have showcased TikTok campaigns' success, such as the